AB0026 Tlr9 stimulation of anergic hcv-associated atypical memory b cells triggers rheumatoid factor autoimmunity by the tnf-Α pathway. (12th June 2018) - Comarmond, C.; Saadoun, D.
Abstract : Background: Hepatitis C virus (HCV) infection contributes to the development of autoimmune disorders, but the mechanisms responsible for HCV-associated autoimmunity are not well understood. Results: Here we show that TLR9 stimulation of atypical memory (AtM) B cells from patients with HCV-associated cryoglobulinemia vasculitis induce the secretion of IFNγ, TNFα but not IL17A by CD4 + CD25 - effector T cells and stimulate their proliferation. Conversely, they reduce the proliferative capacity of CD4 + CD25 hi CD127 -/low FoxP3 + regulatory T cells. TLR9-stimulated AtM secrete TNFα and IgMs with rheumatoid factor activity. We identify a transcriptional signature specific of TLR9-stimulated AtM, centred on TNFα overexpression. AtM B-cell expansions display intraclonal diversity of mutated IgM with features of antigen-driven maturation. AtM-derived antibodies possess rheumatoid factor activity, with each antibody clone targeting a unique epitope on the human IgG Fc region. AtM antibodies are neither polyreactive nor reactive to ubiquitous autoantigens and importantly, not cross-reactive against HCV antigens including NS3 and E2 proteins. Conclusions: These data strongly suggest a central role for AtM in defective tolerance of HCV-CV patients through TLR9 reactivation of anergic AtM and production of IgM antibodies with rheumatoid factor activity. Disclosure of Interest: None declared